Interannual variations in the Zonal Asymmetry of the subpolar latitudes Total Ozone Column during the Austral Spring - Agosta Scarel, Eduardo Andres (2010)
The Southern Hemisphere midlatitude Total Ozone Column (TOC) shows a “horseshoe” like structure with a minimum which appears to have two preferential extreme positions during October: one, near southern South America, the other, near the Greenwich Meridian approximately. The interannual zonal ozone asymmetry exists independently of the variations induced by the 11-year solar cycle, the Quasi-Biennial Oscillation (QBO) and planetary wave activity inducing the Brewer-Dobson circulation. The classification and climatological composition of these two extreme ozone-minimum positions allows for the observations of statistically significant patterns in geopotential height and zonal winds associated with the quasi-stationary wave 1, extending throughout lower stratosphere. The changes in the quasi-stationary wave 1 associated with the extreme TOC positions appear to have sinks and sources determining transient interactions between troposphere and the stratosphere. Thus, distinct climate states in the troposphere seem to be dynamically linked with the state of the stratosphere and ozone layer. The migration of the TOC trough from southern South America to the east during the 1990s can be related to changes in the troposphere/stratosphere coupling through changes in the Southern Annular Mode variability in spring.